2022
DOI: 10.3389/fimmu.2022.968649
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Fusobacterium nucleatum in malignancies except for colorectal cancer: A literature review

Abstract: Fusobacterium nucleatum (F. nucleatum) is originally an oral opportunistic pathogen and accumulating evidence links the presence of F. nucleatum with the pathogenicity, development, and prognosis of colorectal cancer (CRC). However, only limited preliminary data is available dealing with the role of F. nucleatum in other malignancies except for CRC. The present review aims to update and systematize the latest information about the mechanisms of F. nucleatum-mediating carcinogenesis, together with the detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 110 publications
0
8
0
1
Order By: Relevance
“…Through emergent analysis, we can speculate that the role of Fusobacterium nucleatum ( F. nucleatum ) in the Correa cascade of GC development may become a research hotspot in the future. Fusobacterium nucleatum , which exists in the oral cavity and gastrointestinal tract of humans, is an opportunistic pathogen causing systematic diseases, for example, gastrointestinal cancers ( Chen et al, 2022 ; He Z. et al, 2022 ). A number of studies have demonstrated the potential pathogenic role of F. nucleatum in colorectal cancer (CRC; Lee et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through emergent analysis, we can speculate that the role of Fusobacterium nucleatum ( F. nucleatum ) in the Correa cascade of GC development may become a research hotspot in the future. Fusobacterium nucleatum , which exists in the oral cavity and gastrointestinal tract of humans, is an opportunistic pathogen causing systematic diseases, for example, gastrointestinal cancers ( Chen et al, 2022 ; He Z. et al, 2022 ). A number of studies have demonstrated the potential pathogenic role of F. nucleatum in colorectal cancer (CRC; Lee et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the disturbance of the oral microbiome may indirectly promote the occurrence and development of cancers by causing persistent chronic inflammation and suppressing immune response [ 50 , 51 ]. Several studies have shown that the periodontal pathogen Fusobacterium nucleatum might increase the risk of head and neck cancers by indirect carcinogenic effects [ 52 , 53 ]. A recent study revealed that CD8 + T infiltration was decreased in NPC tumor tissues with high bacterial load, indicating that the microbiome may influence NPC by modulating the immune microenvironment [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…F. nucleatum has been shown to promote breast tumor growth and metastatic progression, possibly by preventing the accumulation of tumor-infiltrating T cells in the tumor microenvironment and colonizing breast tumors through D-galactose-β(1–3)-N-acetyl -D-galactosamine (Gal -GalNAc) which binds to Fap2, a surface lectin from F. nucleatum, involved in the colonization of breast cancer. Furthermore, antibiotic therapy with metronidazole suppresses F. nucleatum -induced breast tumor aggravation, indicating that targeting F. nucleatum may enhance breast cancer treatment [ 27 ]. In another detailed study, Parida et al reported that toxin-producing strains of Bacteroides fragilis , when present in the gut or breast tissue, could increase the aggressiveness of breast cancers, induce self-renewal in breast cancer cells and initiate metastatic dissemination to distant organs [ 10 ].…”
Section: The Microbiota Of Breast and Breast Tumormentioning
confidence: 99%